Health Enhancement Program (HEP) Guidelines - Sullivan, Jude; Thurlow, Julie; MacCoon, Donal; Stoney, Catherine; Young, Pam; Lutz, Antoine; Davidson, Richard (My University, 2011)
Guidelines used for implementing the Health Enhancement Program (HEP), a bona fide active control condition for Mindfulness Based Stress Reduction (MBSR)
Keywords: Guidelines; Mindfulness; Control Group